Ze studiów nad symboliką samorządową województwa łódzkiego. Herb gminy wiejskiej ze stolicą w Kutnie - Adamczewski, Marek (Zeszyty Wiejskie, 2016)
In December 2015, after one year of debate on the version of coat of arms, Kutno Municipal Council passed a resolution to establish a coat of arms. Councilors accepted that the coat of arms of Kutno would be a shield on a blue background, with an emblem composed of a red defensive wall, the golden lion with a mirror and a silver lily flower. The image of the coat of arms contains information about Bohdan Zaleski, a poet associated with the municipality of Kutno and the Blessed Virgin Mary, the patron of the church in Głogowiec (near Kutno). The coat of arms of Kutno has been positively evaluated by the Heraldic Commission. Drafts of municipal emblems were prepared by Kinga Łuczak. Coat of arms of Kutno rural commune informs about important facts from the history of the community and its form it refers to the symbols of the city of Kutno and Kutno district.